Thymidine Kinase+/− Mammalian Cell Mutagenicity Assays for Assessment of Nanomaterials - Chen, Tao; Dusinska, Maria; Elespuru, Rosalie (Frontiers in Toxicology, 2022)
The methods outlined here are part of a series of papers designed specifically for genotoxicity assessment of nanomaterials (NM). Common Considerations such as NM characterization, sample preparation and dose selection, relevant to all genotoxicity assays, are found in an accompanying paper. The present paper describes methods for evaluation of mutagenicity in the mammalian (mouse) thymidine kinase (Tk) gene occurring in L5178Y mouse lymphoma cells and (TK) in human lymphoblastoid TK6 cells. Mutations change the functional genotype from TK+/- to TK-/-, detectable as cells surviving on media selective for the lack of thymidine kinase (TK) function. The assays detect a broad spectrum of genetic damage, including both small scale (point) mutations and chromosomal alterations. The mouse lymphoma assay (MLA) is a widely used mammalian cell gene mutation assay for regulatory purposes and is included in the core battery of genotoxicity tests for regulatory decision-making. The TK6 assay is an assay using a human cell line derived similarly via mutagenic manipulations and optimal selection. Details are provided on the materials required, cell culture methods, selection of test chemical concentrations, cytotoxicity, treatment time, mutation expression, cloning, and data calculation and interpretation. The methods describe the microwell plate version of the assays without metabolic activation.